A Water Flow-Like Algorithm for the Travelling Salesman Problem. (7th August 2014) - Srour, Ayman; Othman, Zulaiha Ali; Hamdan, Abdul Razak
Abstract : The water flow-like algorithm (WFA) is a relatively new metaheuristic that performs well on the object grouping problem encountered in combinatorial optimization. This paper presents a WFA for solving the travelling salesman problem (TSP) as a graph-based problem. The performance of the WFA on the TSP is evaluated using 23 TSP benchmark datasets and by comparing it with previous algorithms. The experimental results show that the proposed WFA found better solutions in terms of the average solution and the percentage deviation of the average solution from the best-known solution.